PENGARUH POTENSI KEBANGKRUTAN PERUSAHAAN PUBLIK TERHADAP PERGANTIAN AUDITOR - Theresia Niken Setyorini; Aloysia Yanti Ardiati (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2006)
The main objective of this paper is to examine the effect of failing firms (firms which arepotential to be bankrupt) on auditor switching. Hypothesis was derived from Schwartz and Menon (1985) which implies that failing firms have a greater tendency to switch auditors than healthier firms do. The Z score (Altman model) was used as a proxy to measure the potential of bankruptcy. This method was applied since it has been developed in several countries such as US, Germany, Brazil, Australia, England, Ireland, Canada, the Netherlands, and France. Annual report and Indonesian Capital Market Directory were used to collect the data for a sample of 7 firms that changed their auditors and 7 firms that did not. Those four-teen (14) firms have been selected as sample among firms in consumer goods industries to answer the question about the impact of firns with potential to go bankrupt on auditor switching. Chi-Square result shows that firms with potential to go bankrupt could not influence auditor switching.Keywords: auditor switching, bankruptcy, Altman Z-Score, failing firm